2022
DOI: 10.7150/thno.70098
|View full text |Cite
|
Sign up to set email alerts
|

Cold atmospheric plasma for preventing infection of viruses that use ACE2 for entry

Abstract: Rational: The mutating SARS-CoV-2 potentially impairs the efficacy of current vaccines or antibody-based treatments. Broad-spectrum and rapid anti-virus methods feasible for regular epidemic prevention against COVID-19 or alike are urgently called for. Methods: Using SARS-CoV-2 virus and bioengineered pseudoviruses carrying ACE2-binding spike protein domains, we examined the efficacy of cold atmospheric plasma (CAP) on virus entry prevention. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 104 publications
0
11
0
Order By: Relevance
“…Dai, with his faculties, explored the effect of CAP on mutant SARS-CoV-2 viruses. Their results confirmed that the interaction of • OH and other substances produced by CAP or CAP-activated medium (PAM) could trigger the nuclear translocation of the viral receptor ACE2 and inhibit the SARS-CoV-2 virus to invasive host cells (52). Due to the different complexity of virus particles, viruses infect host cells through a series of strategies, resulting in physical interactions between host cells and viruses.…”
Section: Fungus and Virusmentioning
confidence: 71%
“…Dai, with his faculties, explored the effect of CAP on mutant SARS-CoV-2 viruses. Their results confirmed that the interaction of • OH and other substances produced by CAP or CAP-activated medium (PAM) could trigger the nuclear translocation of the viral receptor ACE2 and inhibit the SARS-CoV-2 virus to invasive host cells (52). Due to the different complexity of virus particles, viruses infect host cells through a series of strategies, resulting in physical interactions between host cells and viruses.…”
Section: Fungus and Virusmentioning
confidence: 71%
“…By contrast, the depth by which plasma-generated compounds can penetrate into virus-infected tissues might be more limited, at least as plasma depth cytotoxicity studies in relevant model systems suggest [ 33 ]. A recent study indicated decreased SARS-CoV-2 uptake via downregulation of its entry port, the ACE2 receptor [ 34 ], upon exposure to long-lived species present in plasma-treated liquids [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The trend observed regarding MCF10A, an epithelial cell line isolated in 1984 from the mammary gland of a 36-year-old white woman with fibrocystic breasts and used by researchers as a healthy cell model [71,72], was opposite to that related to tumor lines.…”
Section: Gc/ms Identification Of Hexanoic Extract Compoundsmentioning
confidence: 96%